Health-related quality of life and its determinants in patients with migraine relating to the coronavirus disease 2019 pandemic in the Eastern Province of Saudi Arabia - Dhafer Alshayban (Journal of Family and Community Medicine)
BACKGROUND: Migraine is a neurological disorder associated with different levels of disability that can impact health-related quality of life (HRQoL). The management of this condition worsened with the challenges posed by the coronavirus disease 2019 (COVID-19) pandemic. This study sought to evaluate the effects of migraine on HRQoL and identify key factors contributing to these outcomes in migraineurs in relation to the COVID-19 pandemic. MATERIALS AND METHODS: A cross-sectional study was carried out on 198 migraine patients between October 2022 and April 2023. HRQoL was assessed using the EQ-5D-5L comprising five domains. Data was collected by both face-to-face interviews and a self-administered online questionnaire. Categorical variables were described as frequencies and percentages while means with standard deviations or medians with interquartile ranges (IQRs) were computed for continuous variables. Chi-square test was used to assess associations of COVID-19 infection with migraine complications and HRQol. RESULTS: The majority of the cohort were predominantly females (67.7%), university graduates (79.8%), and unemployed (63.3%). About 53% of migraineurs who reported no COVID-19 infection, indicated an increase in migraine attacks during the pandemic, whereas 51.9% of the participants who had COVID-19 reported an increase in attacks (P = 0.894). Migraineurs aged <30 years reported a significantly higher HRQoL score (median=0.94, IQR = 0.17, P < 0.001). Participants with higher income levels reported better HRQol (median: 0.89). Those with multi-comorbidities (median= 0.84 vs. 0.99, P < 0.05) showed significantly lower HRQoL. CONCLUSION: Study highlighted significant impact of COVID-19 on increasing frequency of migraine attacks in individuals infected with COVID-19, which in turn led to a decline in HRQol. Correlates of poor HRQoL included advancing age, low income, presence of multiple comorbidities, and unhealthy body mass index. An urgent intervention to improve the HRQol should be implemented after the pandemic.